PERBAIKAN MAINTENANCE UNTUK TARGET AVAILABILITY PENYALURAN GAS DENGAN PENDEKATAN TOTAL PRODUCTIVE MAINTENANCE DI PT PERTAMINA GAS AREA JAWA BAGIAN BARAT - Muhammad Nuramzan Iftari; Rosalendro Eddy Nugroho (Universitas Mercu Buana, 2015)
Abstract: PT Pertamina Gas is a company involved in the midstream and downstream sectors ofgas industry in Indonesia that unreleased from problems that have a relation with level of gastransmission availability which determines the quality and productivity of company intransmitting gas until arrive to the end users. However, maintenance in turbine machinesfrequently conduct reactively which machines fixed if occured a damage (breakdownmaintenance). This is can be seen at availability levels that very fluctuative and declining inmarch 2013 and also december 2013. Therefore, maintenance improvement is required withTotal Productive Maintenance approach so that the gas transmission availability will reach thetarget. TPM is an innovative approach to maintenance that optimizes equipment effectiveness,eliminates breakdowns and promotes autonomous maintenance. According to the primary andsecondary data analysis, planned maintenance programs (one of pillar in TPM) are the maincause of declining the equipment availability in PT Pertamina Gas Western Java Area especiallybecause of spare part problems.Based on this, in order to have gas transmission avalability reachthe target, company needs to conduct Total Productive Maintenance program which includefocused maintenance, autonomous maintenance and planned maintenance.Keywords: Availability, Total Productive Maintenance, Autonomous Maintenance, FocusedMaintenance, Planned Maintenance